Can Greater Transparency improve the Sustainability of Pacific Fisheries?. (February 2022) - Walton, Grant W.; Keen, Meg; Hanich, Quentin
Abstract: International and regional organisations promote transparency on the basis that it can improve the sustainability of fisheries, yet the processes involved, and the outcomes of transparency initiatives, are often opaque and misunderstood. This article examines efforts to improve transparency in the tuna fisheries of the Pacific Island region, with our analysis focusing on members of the Pacific Islands Forum, excluding metropolitan countries New Zealand and Australia. It draws on a tripartite framework to examine transparency initiatives and outcomes associated with the Pacific Islands' tuna fisheries. It finds that efforts to improve transparency have mainly focused on increasing or sustaining economic gains for the region's governments but much less on enhancing transparency of policy-making, decision-making and policy outcomes, especially at the domestic level. Weaknesses in regional and national institutions, and concerns about corruption, overfishing, and sustainability persist. We argue that to improve transparency and sustainability in the fisheries of the Pacific Island region, policy makers and researchers need to better understand and respond to the multiple interests and actors shaping behaviour in the tuna fisheries between different administrative scales. Highlights: This article develops a transparency framework to examine efforts to improve fisheries in the Pacific region. We show how policy makers might better understand and respond to the multiple challenges to transparency in the Pacific.